The media and its impact on the value change of children in the Algerian family - بوغاري هوارية,; بطاوي بهية, (International Journal of Social Communication, 2022)
Children in the Algerian family live a value struggle through everyone who elicits and acquires values from family upbringing and what he acquires from the media (television - social networking sites..). A serious situation that creates a state of imbalance and a kind of confusion and concern and a preference for the authentic traditional values on which the children grew up in the family environment as a result of the process of family upbringing or the new values coming from the West are values that change from the previously mentioned and even contradictory, and this confusion that occurs in the value system of the children for their attempt to prefer values on the other. Does he live in the children within the family environment and imitate the principles, behaviors and attitudes that they acquired from family values, or do they adopt changing immigrant values and abandon traditional values, and the value change occurs in the children as a result of the influence of the media.